Improved ansatz for the direct correlation function in dilute nematic colloids - Sokolovska, T.G.; Sokolovskii, R.O.; Patey, G.N. (Condensed Matter Physics, 2007)
We present an improved analytical ansatz for the colloid-nematic direct correlation function. This ansatz is more accurate than our earlier version, and yields numerical results that are very close to the true mean spherical approximation for dilute nematic colloids. Furthermore, the improved ansatz is valid for external fields of any strength. We examine the zero-field behavior of the colloid-colloid potential of mean force in light of the improved ansatz, and show that at zero field and large separations this function decays as R⁻⁵ and grows as ∑⁶, where ∑ is the colloidal diameter. These dependencies are consistent with our earlier conclusions based on a less accurate version of the ansatz. As with the original ansatz, the improved version remains analytical and can be readily applied to a broad range of physically interesting systems. These include patterned and nonspherical colloids, colloids trapped at interfaces, and nematic fluids in confined geometries, e.g. in droplets.